The pious caliphs - Khan, Majid Ali; Husain, S. Athar (Islamic Book Trust Kuala Lumpur, 1998)
The period of the first four Caliphs is undoubtedly the golden age of Islam and this book deals in detail with the achievements of early Islam in the field of civilization and culture. The author has described the politico-legal system of the Islamic State in the first forty years of Islam